The Mediating Role of Chinese College Students’ Control Strategies: Belief in a Just World and Life History Strategy - Lin, Xuanxuan; Wang, Rongzhao; Huang, Tao; Gao, Hua (Frontiers in Psychology, 2022)
Life history strategies describe and explain how individuals allocate limited resources to survive and develop. Research has found that belief in a just world influences life-history strategies through a sense of control. However, the relationship between a sense of control and a life history strategy is flawed because influencing life-history strategies should be intrinsic to control strategies rather than a sense of control. Based on this view, this paper investigates whether belief in a just world impacts life-history strategies through control striving from the perspective of a life-span theory of control. A total of 408 Chinese undergraduate students completed the Personal Belief in a Just World Scale, Mini-K Scale, and Primary and Secondary Control Scale. Structural equation modelling suggested that belief in a just world can directly or indirectly influence life-history strategies through primary and secondary control strategies, respectively; there was no statistical difference in the degree of influence between the two paths. These results deepen our understanding of the underlying mechanisms in the relationship between belief in a just world and life history strategies, which can be utilized to ensure a slow life history strategy among Chinese university students in the future.